Influence of mixtures of high moisture corn and dry rolled wheat on finishing performance and carcass characteristics - Bock, B.J.; Brandt, Robert T., Jr.; Harmon, D.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Dry rolled wheat and high moisture corn were fed singly and in three combinations in a 132-day finishing trial. Daily gain, feed intake, and final live weight were greatest on the 75% corn:25% wheat diet. Feed efficiencies and carcass characteristics were not affected by grain combination. Daily gain and feed intake tended to decrease as percentage of wheat in the diet increased above 25%.
Keywords: Beef; Corn; Dry rolled wheat; Performance; Carcass characteristics